The Foreign Policy of Donald Trump’s Administration in Transcaucasia - Changiani, Marine (European Scientific Journal, ESJ, 2022)
Transcaucasia is a politically complicated region. Armenia, Azerbaijan, and Georgia have different foreign policy vectors, strategies, and relations with the United States. This paper provides a detailed analysis of the main political processes in Transcaucasia during the presidency of Donald Trump. The research is focused primarily on the development of bilateral relations of the United States with the countries of Transcaucasia in three directions: military cooperation, economic relations, and promotion of democracy. We examine the role and the interests of the United States in Transcaucasia and the priorities of the foreign policy of Trump’s administration there. The role of Russia is significant in the region as well, especially after the 2020 Nagorno-Karabakh war between Armenia and Azerbaijan. The Russian Federation is against losing its dominance there and the expansion of NATO in Transcaucasia. It tries to deepen the authoritarian regime in the region and keep it under its control. The research findings show clearly the importance of cooperation and partnership between this complicated region and the United States, which can be a much better guarantor of stability, development, and democratic progress in Transcaucasia.